PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE DALAM PEMBELAJARAN MATEMATIKA SMK SWASTA PEMBDA NIAS - Harefa, Amin Otoni (IKIP Gunungsitoli, 2012)
abstract. The purpose of the study : 1).Describe the process of learning mathematics by implementing cooperative learning model Think Pair Share.2). Describe the average math learning outcomesby implementing cooperative learning model Think Pair Share. 3). Proves significantly better quality of mathematics learning process by implementing cooperative learning model Think Pair Share.4). Prove significantly the average math learning outcomes either by implementing cooperative learning model Think Pair Share . This research was conducted at SMK Swasta Pembda Nias with research subjects were students of class XII TGB 1st semester academic year 2011/2012 , amounting to 40 people . This study is an action research (CAR), which consists of two cycles with the subject matter of chance . Research instruments : 1). Observation sheet , consisting of (a) the observation sheet for students who are not active in the learning process (b) observation sheet for students who are actively involved in the learning process (c) observation sheets for teachers. 2). Achievement test , (3) Questionnaire quality of learning , (4) The interview . Results of the study : 1). The quality of the learning process through the application of mathematical learning model Think Pair Share . Average results of the questionnaire at the end of the first cycle was 78 % belonging to either category and at the end of the second cycle was 89 % belonging to either category at all, 2). Average mathematics learning outcomes through the application of learning model Think Pair Share . Average learning outcomes at the end of the first cycle are classified as either category and 78.86 at the end of the second cycle was 81.70 classified as either category . Percentage of mastery learning in the first cycle to 78 % , while in the second cycle percentage reached 95 % mastery learning , 3). Based on the results of the Z test for hypothesis testing measures the quality of learning , Zhitung = 1.97 value obtained was further confirmed by Ztabel value = 1.64 at 5 % significance level ( α = 0.05 ) . Because Zhitung > Ztabel , then Ha is accepted and H0 is rejected , so it is concluded that the hypothesis :